Long‐term safety and efficacy of nucleo(t)side analogue therapy in hepatitis B. (10th February 2018) - Buti, Maria; Riveiro‐Barciela, Mar; Esteban, Rafael
Abstract: Long‐term treatment of chronic hepatitis B (CHB) with nucleos(t)ide analogues is often necessary to achieve durable viral suppression. Therefore, current guidelines recommend the most potent drugs with optimal resistance profiles. Entecavir (ETV), tenofovir disoproxil fumarate (TDF) and tenofovir alafenamide (TAF) are the first‐line monotherapies for CHB. All of these drugs are highly effective in suppressing viral replication but with slightly different safety profiles. This review provides an overview of the long‐term efficacy and safety data that have become available over the 10 years since ETV and TDF were first approved for the treatment of chronic hepatitis, and recent data on TAF in patients with CHB.